Peran Kepemimpinan TNI dalam Mencapai Tujuan Organisasi di Lanud Suryadarma - Asri Nurwardah; Ira Hamidatul Apiah; Ahmad Farihin; Muhammad Jali Rokhani (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2023)
TNI AU Suryadarma Air Force Base is one of the operational bases under the command of Koopsau I. Its main task is to ensure the operational readiness of helicopter aircraft and provide guidance to its subordinate units. Logistic components, including facilities and installations, play a crucial role in the success of aviation operations. The vision of Lanud Suryadarma is to become a professional, militant, innovative, and respected unit, with a focus on producing skilled helicopter pilots. This research utilizes a qualitative descriptive approach with a case study as the research method. Data is collected through interviews, observation, and documentation. The practical work unit is conducted at TNI AU Lanud Suryadarma, involving various tasks such as filing, manuscript delivery, and document management. Lanud Suryadarma has functions in unit development, equipment maintenance, aerospace potential development, and coordination with relevant agencies. Leadership also plays an important role in the organization, including Lanud Suryadarma. This research provides an understanding of the factors that contribute to operational success and offers insights for future improvements.